The solid-state, solution and gas-phase interactions of diphosphane monooxide spacers with heavier group 8,9 transition metals and gallium in novel organometallic assemblies: An experimental and computational study - Monakhov, Kirill; Zessin, Thomas; Linti, Gerald W. (Journal of organometallic chemistry, 2012)
Six new mono-substituted carbonyl clusters [M3(CO)11(DPMO)] (M = Os, Ru; 1-4) and [Rh6(CO)15(DPMO)] (5, 6) were obtained from the reactions of non-symmetrical bifunctional diphosphane monoxides (DPMOs, Ph2P(CH2)nP(O)Ph2, n = 2, 3) with triangular clusters [Os3(CO)12] and [Ru3(CO)12], and octahedral cluster [Rh6(CO)15(NCMe)] under mild conditions. 1-6 were then subjected to electrophilic reactions with GaCl3, which resulted in coordination-based molecular assemblies [M3(CO)11(DPMO)(GaCl3)] (M = Ru, Os; 7-10) and [Rh6(CO)15(DPMO)(GaCl3)] (11, 12). 1-12 were characterised by 31P{1H} NMR, IR spectroscopy, and FAB mass spectrometry. The crystal structures of 1, 2 and 7 were determined by single-crystal X-ray analysis. 7 is the first solid-state characterised Os-Ga bridged complex. The latter and its constitutive fragment, 1, were studied by density functional calculations in the gas phase and in solution in order to better understand their structural features. Two different rotameric structures related by rotation about the P-C-C-P linkage of the DPMO ligand were established for 1 and 7. The bonding properties of 7 were analysed by means of a quantitative energy decomposition analysis (EDA). The EDA revealed a predominant electrostatic character for the interactions between the three units (carbonyl cluster, gallium halide and spacer) constitutive of 7.